Volume 1: Symposia, Parts a and B 2005
DOI: 10.1115/fedsm2005-77015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flow Phenomena Related to the Unstable Energy-Discharge Characteristic of a Pump-Turbine in Pump Mode

Abstract: Regions of positive slope in the pressure-discharge characteristics are one of the major concerns in design and operation of centrifugal pumps, as they are limiting the admissible operating range to values above the critical discharge. The industrial pump turbine of specific speed ν=0.42 (n q =66 min -1 ) proposed as QNET-CFD test case TA6-04 shows a marked saddle in the energy-discharge characteristic associated to a sudden drop of efficiency versus discharge at part load. The pump-turbine consists of a shrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…As a consequence, more and more researchers have focused on studies of the hump instability characteristic using experimental and numerical methods. The hump characteristic is mainly caused by the prerotation, recirculation [1], and suction surface cavitation [2] at the runner inlet, backflow and vortex motion [3], rotating stall [4,5], and secondary flow pattern [6] in the diffuser channels. Lots of achievements have been obtained, which provide a deep understanding of the hump characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, more and more researchers have focused on studies of the hump instability characteristic using experimental and numerical methods. The hump characteristic is mainly caused by the prerotation, recirculation [1], and suction surface cavitation [2] at the runner inlet, backflow and vortex motion [3], rotating stall [4,5], and secondary flow pattern [6] in the diffuser channels. Lots of achievements have been obtained, which provide a deep understanding of the hump characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, more and more researchers have focused on studies of the hump instability characteristic using experimental and numerical methods. The hump characteristic is mainly caused by the prerotation, recirculation [1], and suction surface cavitation [2] at the runner inlet, backflow and vortex motion [3], rotating stall [4,5], and secondary flow pattern [6] in the diffuser channels. Lots of achievements have been obtained, which provide a deep understanding of the hump characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…The flow mechanism of a pump-turbine in pump mode is still not clear, especially for the drooping zone. Braun et al (2005) and Braun (2009) studied unstable energy-discharge characteristics of an industrial pump-turbine in pump mode and concluded that flow patterns, energy and velocity distributions at the rotor-stator interface are related to the onset of recirculation. However, the research just used one channel per component, which could not reflect interaction among the channels.…”
Section: Introductionmentioning
confidence: 99%